2009
DOI: 10.1177/02601079x09002100204
|View full text |Cite
|
Sign up to set email alerts
|

Developing Energy-based Poverty Indicators for South Africa

Abstract: Energy provision and the role it plays in poverty alleviation is well documented. South Africa has an ambitious poverty alleviation program of halving 2004 poverty levels by 2014, which demands an increase in the provision of energy to both urban and rural impoverished areas. Yet the country has no energy based poverty indicators to guide such policy. This paper attempts to fill that gap by developing reliable, theoretically rigorous energy based indicators from extant data gathered in the 2005 South African h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…However, the methodology described above was developed by Kemmler and Spreng (2007), based on Pachauri and Spreng (2004), who found that the weighting was robust for Indian data. The method was applied to South African Income and Expenditure Survey data by Vermaak et al (2009), who conducted considerable sensitivity analysis regarding the accessibility weighting scheme as well as the other assumptions made during the course of the analysis. The estimation of energy poverty was found to be robust to these assumptions, establishing confidence that this methodology can be reliably applied to South African household survey data (Vermaak et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the methodology described above was developed by Kemmler and Spreng (2007), based on Pachauri and Spreng (2004), who found that the weighting was robust for Indian data. The method was applied to South African Income and Expenditure Survey data by Vermaak et al (2009), who conducted considerable sensitivity analysis regarding the accessibility weighting scheme as well as the other assumptions made during the course of the analysis. The estimation of energy poverty was found to be robust to these assumptions, establishing confidence that this methodology can be reliably applied to South African household survey data (Vermaak et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The method was applied to South African Income and Expenditure Survey data by Vermaak et al (2009), who conducted considerable sensitivity analysis regarding the accessibility weighting scheme as well as the other assumptions made during the course of the analysis. The estimation of energy poverty was found to be robust to these assumptions, establishing confidence that this methodology can be reliably applied to South African household survey data (Vermaak et al, 2009). This access-adjusted useful energy unit measure is applied to the data set in quantifying the incidence of energy poverty in South Africa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Tait (2017) and Israel-Akinbo et al ( 2018) conducted studies on measuring energy poverty in low-income households in South Africa and concluded that higher income levels reduce energy poverty. Unlike other studies, Vermaak et al (2009) analyzed the effects of government policies on energy poverty. El-Katiri (2014) examined the problem of energy poverty in oil-rich countries in the Middle East and North Africa and emphasized that energy poverty is caused by problems in domestic distribution.…”
Section: South African Countriesmentioning
confidence: 99%
“…Energy poverty, according to Ogwumike and Ozughalu (2016), Ahmed andGasparatos (2020), andBazilian et al (2012), has a detrimental effect on economic growth. Selcuk et a l (2019), , Vermaak et al (2009), El-Katiri (2014), Nathan and Hari (2020), Jayasinghe et al (2021), Huang et al (2022), Olang et al (2018), Bouzarovski et al(2012, Tait (2017), Ssennono et al (2021) and Piwowar (2020) conclude that low-income households are more likely to face energy poverty. Israel-Akinbo et al (2021), Sokolowski (2020), Barnes et al (2011) and Nduka (2021) explain that rural households are more affected by energy poverty than other households.…”
Section: South African Countriesmentioning
confidence: 99%